"Ain't no white people have to be cultural ambassadors, right?" How a Latinx teacher in the US South resists ephemeral multiculturalism for political praxis. Issue 4 (2nd October 2021) - Monreal, Timothy; Floyd, Reina
ABSTRACT: In this article, we expand the geographic narratives of Latinx teachers by first outlining how such teachers are desired to be a certain type of "cultural ambassador" in the US South, and second, how one teacher eschews this construction to instead center political agency and a democratic praxis toward racial justice. Whereas cultural ambassadorship privileges an ephemeral discourse of diversity and post-racism that positions Latinx teachers as objects tasked to model and replicate "safe" multiculturalism, we share how one Afro-Latina teacher in South Carolina uses her power to teach students how to interrogate racist systems and to practice political resistance.